DESAIN LKPD BERORIENTASI KOMPLEKSITAS KONTEN DAN PROSES KOGNITIF PADA MATERI DINAMIKA GERAK BENDA UNTUK PEMBELAJARAN FISIKA KELAS X SMA/MA - Dila Alhumaira; Amali Putra; Yenni Darvina (Universitas Negeri Padang, 2017)
This research was motivated by the low of knowledge level of competence from content complexity’s aspects and cognitive levels process that must be mastered by high school students in Padang. The result of observations indicate that it is caused by several factors, one of factor is the unavailable student worksheet (LKPD) as a physics learning materials Padang’s high schools which refers to content complexity and cognitive process as implied by 2013’s curriculum. This study has purpose to produce preliminary analysis to LKPD oriented to content complexity and cognitive process in material dynamics of object motion for physics learning in tenth grade students of Senior High School or Islamic Senior High School, produces shapes LKPD that has been designed, and to know quality of LKPD designed. Type of this research is (Research and Development / R & D) using 4D models that consist of four stages which are define, design, develop and disseminate in a limited test. Validator consist of three Physics lecturer and tenth grade students as a subject of research. Data of this study include qualitative data obtained from observation, interviews and analysis of documentation and the quantitative data obtained from the validity, practicality and knowledge competency score after using LKPD . The data have been analyzed by using test validity and practicalities to determine the quality criteria of LKPD is in the design and test of effectiveness is limited by using N-Gain test to know the effectiveness of the use of LKPD is in the design of the study of students through pretest and posttest. Based on analysis of qualitative data obtained that have been made stating that the required LKPD containing dimensions of knowledge and cognitive process are complete to improve the competence of learners to fit the curriculum mandated by 2013. Based on the analysis of quantitative data, obtained an average score of 3.46 validity with very valid criteria, the average score of 3.50 practicalities by teachers with very practical criteria and an average score of 3.47 on the responses of learners is very agreed with the criteria as well as the average score of the study of students through the test with limited effectiveness N-Gain test was 0.51 are in the middle criteria, so we concluded that LKPD who has designed a decent used to improve the competence of Physics learners